Assessing Communicative Competence: Validity of Tests in CLT-Based English Classrooms Across Formal in West Java - Fella Rosy; Nida Husna; Ummi Kulstum; Muhammad Farkhan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research examines the validity of classroom tests in formal secondary schools in West Java, Indonesia, which purport to practice Communicative Language Teaching (CLT). Although CLT calls for the development of communicative competence encompassing grammatical, sociolinguistic, discourse, and strategic components, concerns arise that classroom testing procedures may fail to represent these communicative objectives. Data were gathered from four EFL teachers using a qualitative multiple case study design through document analysis and a semi-structured online questionnaire. Results show that although the participants exhibit firm theoretical grasp of communicative assessment and include performance tasks like interviews, role plays, and video-based speaking tasks, complete alignment with CLT ideals is limited. A number of challenges impede implementation, such as lack of professional development, large class sizes, limited instructional time, and institutional requirements for grammar-dominated tests. This study concludes that despite claimed allegiance to CLT, the validity of tests utilized in these classrooms continues to be inconsistent. It suggests enhancing teacher assessment literacy, instituting prolonged training, and reforming institutional policy to accommodate communicative assessment practices more in accord with CLT.